Surface properties of friction stir welded dissimilar joints of AA7075 and Mg-WE43 alloys: Effect of positional arrangement - Tariq Ahmad; Nadeem Fayaz Lone; Noor Zaman Khan; Babar Ahmad; Arshad Noor Siddiquee; Daolun Chen (Journal of Magnesium and Alloys)
This study investigates the surface properties of the dissimilar AA7075/Mg-WE43 joints wherein the effect of positioning the AA7075 on the advancing or retreating sides during friction stir welding (FSW) was scrutinized. The EBSD analysis revealed that the average grain size reduced from 4.11 ± 0.7 µm to 2.04 ± 0.9 µm when AA7075 was shifted from advancing to retreating side. The results showed that positioning AA7075 on the retreating side significantly reduced the wear rate from 0.41 mm³/Nm to 0.27 mm³/Nm and mitigates the problem of brittle intermetallic compound (IMC) formation, consequently reducing the average microhardness. Corrosion resistance improved from 77.59 mpy to 56.299 mpy. The higher grain refinement improved wear resistance due to higher grain boundary density and greater chances of formation of protective oxide films. The current work thus enhances the practical applicability of AA7075/Mg-WE43 welds for lightweighting of automotive structures.